Kidney transplantation and its vascular surgical complications (Research, Society and Development, 2023)
Among the complications of kidney transplantation, it is noted that they can be classified as pathological or surgical, and these can affect graft function and cause significant morbidity in the recipient. Bleeding is uncommon after kidney transplants, but it usually occurs from unligated vessels at the hilum of the graft or from small retroperitoneal vessels sectioned from the recipient, and risk factors in the recipient for this event include obesity and use of anticoagulants. Furthermore, vascular complications may involve the donor vessels (renal artery and renal vein), the recipient vessels (iliac artery), or both. Renal artery stenosis is a more frequent late complication, and is much more common than renal artery thrombosis, with the site of anastomosis being the most common. Among the risk factors, atherosclerotic disease of the recipient, inappropriate suturing technique and trauma to the donor artery stand out. Furthermore, venous thromboembolic complications that affect recipient vessels (deep vein thrombosis and pulmonary embolism) are not uncommon. Typically, two peaks of incidence are reported: one early in the postoperative period (probably related to operative factors) and a second peak around four weeks (perhaps related to an increase in hematocrit level). Risk factors include age of recipient greater than forty years, diabetes mellitus, thrombophilic disorders, and history of deep vein thrombosis. In addition, lymphoceles, which are fluid collections of lymph that usually result from lymphatic vessels cut during surgery, can also constitute a complication.